2007
DOI: 10.1002/adfm.200601172
|View full text |Cite
|
Sign up to set email alerts
|

Organic Solar Cells by Annealing Stacked Amorphous and Microcrystalline Layers

Abstract: Organic solar cells were fabricated by stacking aromatic amine and C60 layers. The energy conversion efficiency of these solar cells was low because of poor photoabsorption by these layers and short diffusion length of excitons. However, the photocurrent density was increased by about 3 times by the application of heat treatment to the stacked organic layers at 140 °C, and the maximum energy conversion efficiency reached 1.1 % under AM 1.5, 100 mW cm–2 simulated solar light. The internal quantum efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…The device exhibited an open circuit voltage ( V OC ) of 0.92 ± 0.01 V, a J SC of 2.6 ± 0.1 mA cm −2 , a fill factor (FF) of 0.71 ± 0.02, and a power conversion efficiency ( η ) of 1.7% for the incident AM1.5G light at 100 mW cm −2 , respectively. As compared with the reported performance ( J SC: 1∼4 mA cm −2 , V OC : 0.3∼0.9 V, FF: 0.3∼0.5, and η : 0.1∼1.3% under white light irradiation) of OPVs using amorphous molecular materials,31, 34, 35, 37–42 Device A exhibited higher V OC , FF and η values⋅ In particular, the FF value for Device A was very high, being comparable to those reported for pn‐heterojunction OPVs using polycrystalline CuPc 1…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The device exhibited an open circuit voltage ( V OC ) of 0.92 ± 0.01 V, a J SC of 2.6 ± 0.1 mA cm −2 , a fill factor (FF) of 0.71 ± 0.02, and a power conversion efficiency ( η ) of 1.7% for the incident AM1.5G light at 100 mW cm −2 , respectively. As compared with the reported performance ( J SC: 1∼4 mA cm −2 , V OC : 0.3∼0.9 V, FF: 0.3∼0.5, and η : 0.1∼1.3% under white light irradiation) of OPVs using amorphous molecular materials,31, 34, 35, 37–42 Device A exhibited higher V OC , FF and η values⋅ In particular, the FF value for Device A was very high, being comparable to those reported for pn‐heterojunction OPVs using polycrystalline CuPc 1…”
Section: Resultsmentioning
confidence: 78%
“…Amorphous molecular materials, i.e., small organic molecules that readily form stable amorphous glasses with well‐defined glass‐transition temperatures ( T g s),29, 30 are also expected to be good candidates for materials in OPVs for their practical use and have been receiving growing attention. Amorphous molecular materials which have hitherto been studied as OPV materials include 4,4′,4″‐tris[5‐(dimesitylboryl)thiophen‐2‐yl]triphenylamine,31 4,4′,4″‐tris[4‐nitrophenyl(4‐methylphenyl) amino]triphenylamine,31 4,4′,4″‐tris[3‐methylphenyl(phenyl)amino]triphenylamine ( m ‐MTDATA),32, 33 N , N ′‐diphenyl‐ N , N ′‐bis(3‐methylphenyl)benzidine (TPD),33, 34 N , N ′‐diphenyl‐ N , N ′‐di( α ‐naphthyl)benzidine ( α ‐NPD),35 siloles containing carbazolyl groups,36 π‐conjugated systems consisting of triphenylamine and oligothiophene,37 triarylamine‐substituted carbazole‐based dendrimers with an oligothiophene core,38 perylene diimide derivatives,39 diphenylaminofluorenyl‐capped thiadiazoloquinoxaline,40 π‐conjugated systems consisting of triphenylamine and benzothiadiazole,41 and dithiafulvenyl‐derivatized triphenylamines 42. It has been reported that OPVs using these amorphous materials exhibit power conversion efficiencies of 0.1∼1.3% under white light irradiation with a Xe lamp or under air‐mass (AM) 1.5G illumination at intensities of 97∼100 mW cm −2 31, 34, 35, 37–42.…”
Section: Introductionmentioning
confidence: 99%
“…There are usually two possible techniques to overcome the limitation: preparing bulk heterojunction by co-evaporating two materials to form a blend film; optimizing the thickness, molecular order and the morphology of organic materials. 4,5 In order to modify the structures of bulk heterojunction, controlling the growth condition [6][7][8] or introduction of buffer layers 9,10 has been investigated. High PCEs of 5-6% for single OPV cell have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This chemistry should help in the design of novel materials with space‐separated donor–acceptor regions. The simultaneous presence of intrinsic donor–acceptor characteristics in some of these molecules should also allow the investigation of heterojunctions formed in the resulting materials 20b. Along with the possibility for S N Ar fluorine displacement, our method paves the way to the formation of a huge number of helically chiral molecules from a common precursor.…”
Section: Methodsmentioning
confidence: 96%